Actualization of Archiepelagic Concept in Legal Curriculum to Create Integrity Law Graduates - Diniyanto, Ayon (The Indonesian Journal of International Clinical Legal Education, 2019)
According to the Constitution of 1945 Indonesia recognized as a rechstaat, which means that every State activities have to be based on legal formal instrument. Meanwhile, in the practical, law enforcement in Indonesia still not appropiate as people as expected. Many factors lead to poor law enforcement in Indonesia from the legal substance, legal structure, and legal culture. The condition is certainly very problematic when law enforcement cannot enforce the justice. Its means there are various factors lead the poor quality of law enforcement in Indonesia. Educational factor on the legal study is fundamental to create law enforcement with integrity and fairness. No wonder when the legal education into the public spotlight rarely. The legal education have not been able optimally to create law enforcement with integrity.